Primary breast lymphoma in the right breast during treatment for left breast cancer - Nagata, Shigeyuki (BioMed Central, 2007)
BACKGROUND: Primary breast lymphoma is a rare condition, and distinguishing it from breast cancer is important because their treatments differ radically. Moreover, a recent report showed that mastectomy offered no benefit in the treatment of primary breast lymphoma. CASE PRESENTATION: A 59-year-old woman was treated with adjuvant chemotherapy and local radiation after surgery for left breast cancer. She presented with a rapidly growing mass in the right breast at 20 months after surgery. Mammography and computed tomography revealed a massive tumour. She was diagnosed with primary breast lymphoma by aspiration cytology, and surgery was performed. Histopathological and immunohistochemical findings confirmed a diffuse large B-cell type primary breast lymphoma. CONCLUSION: In this case, the lymphoma exhibited rapid growth despite chemotherapy for a malignancy in the contralateral breast. The patient had developed bronchiolitis obliterans organizing pneumonia due to radiation. Therefore, surgical treatment of the lymphoma was selected.